Ascorbic acid therapy: A potential strategy against comorbid depression-like behavior in streptozotocin-nicotinamide-induced diabetic rats - Shivavedi, Naveen; Gullanki Naga Venkata Charan Tej; Kaushik Neogi; Prasanta Kumar Nayak (Elsevier Masson SAS, 2018)
This study examined the potency and efficacy of ascorbic acid (AA) in the management of depression-like behavior in diabetic rats. Diabetes mellitus was induced by single intraperitoneal injections of nicotinamide (120 mg/kg) and streptozotocin (65 mg/kg) administered 15 min apart. Diabetic (blood glucose ≥250 mg/dL) rats were subjected to intermittent foot-shocks to induce comorbid depression. Seven groups of diabetes comorbid depressed rats received vehicle (1 mL/kg) or AA (10, 25, 50, 100, 200, or 400 mg/kg) orally for eleven days. Three control groups namely- nondiabetic, diabetic, and depressed rats received the vehicles only. The potency (ED50) and efficacy (Emax) of AA against immobility period, hypercorticosteronemia, adrenal hyperplasia, hyperglycemia, hypoinsulinemia, oxidative stress, and inflammatory response were estimated. AA administration caused a dose-dependent decrease (P < 0.05) in immobility period with maximum inhibition of 69% (efficacy) at 200 mg/kg and ED50 of 14 mg/kg (potency). AA at 200 mg/kg produced the maximal reduction in hypercorticosteronemia (55.1%) and adrenal hyperplasia (52.6%) with ED50 of 9.8 and 14.4 mg/kg, respectively. AA at 400 mg/kg produced the maximal reduction in hyperglycemia (35.5%), hypoinsulinemia (32.7%), and lipid peroxidation (82%) with ED50 of 18.6, 13.7, and 20.7 mg/kg, respectively. Moreover, AA at 400 mg/kg produced the maximal increase in SOD content (83%), CAT activity (77.9%), and IL-10 level (63%) with ED50 of 21.5, 21, and 21 mg/kg, respectively. In conclusion, the present results suggest that AA has therapeutic potential against diabetes comorbid depression but better regulation of hyperglycemia and hypoinsulinemia is required to achieve maximal benefits.
Keywords: Diabetes comorbid depression Ascorbic acid Forced swim test Hyperglycemia Oxidative stress IL-10